THE EXPRESSION OF HER-2 AND GALECTIN-3 IN COLORECTAL ADENOCARCINOMA AND THEIR RELATIONSHIP WITH CLINICOPATHOLOGICAL PARAMETERS - Lesmana, Vienna Alodia (UNIVERSITAS BENGKULU, 2020)
Colorectal carcinoma (CRC) is the third most common cancer among worldwide. Data from WHO GLOBOCAN in 2018 show there were 1.8 million cases of CRC in the world, with mortality rates 861,000. Histopathology of tumor show 90% of CRC is adenocarcinoma and predominantly in men. Some proteins that are thought to play a role in tumor development are HER2 and Galectin-3. Correlation between expression of Human Epidermal Growth Factor Receptor 2 (HER2) and Galectin-3 with clinicopathology aspect are expected to help determine treatment options. The aim of this study was to investigate the correlation between expression levels of HER-2 and Galectin-3 in vary clinicopathological aspect of colorectal adenocarcinoma. Cross sectional study was conducted in 40 samples of colorectal adenocarcinoma in dr. Kariadi Central General Hospital from 1st January 2018 until 31st December 2018. Samples were analyzed regarding the expression of HER2 and Galectin-3 by immunohistochemical staining of paraffin-embedded material. Coexpression of HER-2, Galectin-3 and the clinicopathological parameters (gender, age, location, depth of invasion, lymph nodes metastase, distant metastase and stage) were analyzed using Chi square test and Spearmans correlation test. Positive HER-2 expression was found on 5% of samples, while strong expresion of Galectin-3 was found on 12.5% of samples. There was no significant correlation between HER-2 and Galectin-3 expression and clinicopathology aspect.